2020
DOI: 10.1007/s10943-020-01069-6
|View full text |Cite
|
Sign up to set email alerts
|

Socio-religious Prognosticators of Psychosocial Burden of Beta Thalassemia Major

Abstract: The study investigates the socio-religious factors in the propagation of genetically inherited disease of Beta thalassemia. The disorder which reportedly has a significant protraction through repeated cousin marriages results in the social maladjustment of the parents of the sick children due to constant depression, anxiety, and weak social interaction and may lead to social isolation as well. This research aims to find out the significant effect of socio-religious trends on psychosocial burden of beta thalass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…A study among children with thalassaemia found that these children tend to be introverted and emotionally unstable in their personality characteristics, which were mainly manifested as being alone, withdrawn, indifferent to others, inactive, socially passive, low self-confidence, sensitive, depressed, insomnia, anxiety, depression, etc [28]. Psycho- Therefore, alleviating the children's negative emotions through psychological flexibility, helping the children to recover, rebuilding their confidence in life and promoting physical and mental health should also be the focus of medical practitioners today [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A study among children with thalassaemia found that these children tend to be introverted and emotionally unstable in their personality characteristics, which were mainly manifested as being alone, withdrawn, indifferent to others, inactive, socially passive, low self-confidence, sensitive, depressed, insomnia, anxiety, depression, etc [28]. Psycho- Therefore, alleviating the children's negative emotions through psychological flexibility, helping the children to recover, rebuilding their confidence in life and promoting physical and mental health should also be the focus of medical practitioners today [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of social support causes immense psychosocial burdens to patients and families. Therefore, support from family, friends, community, and medical professionals is essential to confront the disease and overcome the burden [ 33 ].…”
Section: Reviewmentioning
confidence: 99%
“…Lack of knowledge of the causes of disease and its treatment, along with social, cultural, and religious factors, adds to the psychosocial burden. Therefore, the efficacious therapeutic intervention of thalassemia requires an all-inclusive scientific understanding, interpretation, and perception regarding β-thalassemia major [ 33 ]. Long-term psychosocial support is required to help reduce emotional distress, improve compliance with treatment and strengthen coping strategies to improve the quality of life for thalassaemic cases and related family members [ 25 , 34 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations